SIMULASI PENGARUH RISIKO SUPPLY CHAIN TERHADAP KETERLAMBATAN PENGADAAN MATERIAL BAJA TULANGAN DENGAN METODE MONTE CARLO - Ainal Hamdah Aritonang; Greecencia M. Limbong; Jati Utomo Dwi Hatmoko; Frida Kistiani (Jurnal Karya Teknik Sipil, 2016)
Work on the building project requires a material that is more complex and involves many parties so that the building project has a high complexity compared to other civilian buildings. One of the complexity of such problems in the procurement of materials. Some of the things that causes this problem is the existence of an uncertainty in the supply of construction materials. Reinforcement steel is the main ingredient in development , especially the construction of the building. The need of reinforcing steel required at each work ranging from foundation work , beams , plates and columns. Therefore, the availability of steel reinforcement is a major priority so that there should be no delay in procurement. Delays of this material may be caused by uncertainties in procurement activity. Uncertainties in the procurement of materials sourced from four stages: stage supply chain activities supply, control, process, and demand. The stages of the supply chain to be a reference to analyze the possibility of delays in the procurement of a material. Thus, this study aims to determine how much time minimum and maximum time delay procurement of materials, the maximum possible delay in work activities and work activities that are most likely and dominant risk that affects the delay procurement of materials for steel material. The major delays in the procurement of material obtained from the analysis of probability and risk impact with monte carlo method and application assistance crystal ball. In the procurement of steel material analysis showed that a minimum delay of 2.20 days,17.05 days maximum, the maximum possible delay in work activities 15.05 days, and delays in work activities that are most likely 9.24 days. Sources of risk that affect the delay is on the demand stage that ordering additional material due to design changes, material delivery delays due to financial problems, and ordering additional material due to changes of function space.